Interrelation between the Author and the Text in W. S. Burroughs’s Naked Lunch and Chuck Palahniuk’s Fight Club - Viktoria Grivina (Pitannâ Lìteraturoznavstva)
Article adopts Jacques Lacan’s concept of the “mirror stage” to study the mechanisms of the way the Author’s identity evolves in W. Burroughs’s Naked Lunch and Ch. Palahniuk’s Fight Club. Evolution of the Author is set against general process of personal growth. The study is primarily concerned with features of the Author’s evolution within transgressive fiction, as Chuck Palahniuk and William Burroughs are the key figures of this genre. Transgression presupposes addressing social taboos by explicating them, thus creating strong reactions within the readership. We argue and find evidence that Burroughs and Palahniuk in the process of facing their perfect images of the Author digress from what Lacan would consider normal development. When they are given a chance to produce a unified body of text, the writers chose unconscious strive for fragmentation instead. Fragmented images invade Naked Lunch and Fight Club. However the mirror stage in the case of Palahniuk and in the case of Burroughs differ. While Burroughs in the myth of the Interzone ends up rejecting the notion of unique Author as such, Palahniuk accepts the fact that he managed to form a new niche for transgressive fiction and stays true to this niche, continuing similar aesthetics in the works that follow.